KONFLIK PSIKOLOGIS TOKOH YUDHIS DALAM NOVEL "POSESIF" KARYA LUCIA PRIANDARINI - Pemila, Chichi (Jurnal Bahastra, 2021)
This study aims to describe how the factors that cause psychological conflict and the consequences of psychological conflict on the character Yudhis innovel Posesif Lucia Priandarini's. The method used is descriptive qualitative method using data collection techniques, namely the data is read, the data is marked, the data is grouped, the data is analyzed, the data is presented, the data is concluded. Based on the research conducted by the researcher, it can be concluded that there are seven factors that cause psychological conflict and four consequences that arise from the psychological conflict of Yudhis character innovel Posesif Lucia Priandarini's.